Craniofacial morphology of class III malocclusion with DUSP6 gene: Mutation and non-mutation groups - Nowrin, Shifat A; Basri, Rehana; Alam, Mohammad Khursheed; Yusa, Tatsunori; Nakano, Junzaburo; Jaafar, Saidi; Mokhtar, Khairani Idah; Osuga, Naoto (The Hard Tissue Biology Network Association, 2016)
The etiology of developing class III malocclusion and the role of craniofacial structures in this phenotype remain indistinct. The purpose of this study was to compare the relative relationship of craniofacial structures of DUSP6 gene mutation and non-mutation groups in class III malocclusion of Malaysian Malay families and their three generations. Thirty class III cephalometric radiographs of ten Malaysian Malay families including three generations with an average age 23, 54 and 79 years of each generation respectively were studied. All landmarks were positioned, determined and consequently tracings were completed Romexis software (Planmeca, Finland) to accomplish craniofacial morphology investigation. The statistical comparisons of the mutation and non-mutation group were conducted with independent t test and analysis of variance (ANOVA) was applied to evaluate the values for three generations in class III malocclusion among all measurements. The result of the current study revealed that in mutation group, there are significant differences in Co-Gn-B and SN-MDP variables compare to non-mutation group. However, almost all craniofacial variables show no significant differences among three generations. This study may suggest that in mutation group mandible is more deviated from cranial base compare to non-mutation group and there are virtually no skeletal changes among three generations with age in case of growing class III malocclusion.